(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Gross motor development is a fundamental aspect of children’s growth and plays an important role in supporting physical, cognitive, social, and emotional development. However, limitations in learning models and the lack of innovative physical education activities often reduce opportunities for elementary school students to optimally develop their gross motor skills. Therefore, this study aimed to develop a gross motor game model for elementary school students at SD Inpres 2 Birobuli that is feasible, attractive, and effective for use in Physical Education, Sports, and Health (PJOK) learning. This study employed a Research and Development (R&D) approach focusing on the development of a game-based learning module. The development process consisted of four stages: needs analysis, product design, expert validation, and product revision. Data were collected through observations, interviews, and expert validation questionnaires involving a material expert, a media expert, and a practitioner expert (PJOK teacher). The results revealed that the developed model was considered feasible and appropriate for implementation in elementary school learning. The validation scores reached 77.34% from the media expert, 87.50% from the material expert, and 98.04% from the practitioner expert. Furthermore, the combined validation results showed that all developed games were categorized as highly valid, with Game 1 obtaining 93.2%, Game 2 84.9%, Game 3 86.5%, and Game 4 85.4%. In conclusion, the developed gross motor game model is highly feasible and valid for supporting gross motor skill development among elementary school students. The model can serve as an innovative learning resource that helps teachers create more engaging, enjoyable, and effective physical education learning experiences.